Taxonomic status and ecology of Oriental Pheretima darnleiensis (Fletcher, 1886) and other earthworms (Oligochaeta : Megascolecidae) from Mt Kinabalu, Borneo - Blakemore, Robert J.; Csuzdi, Csaba; Ito, Masamichi T.; Kaneko, Nobuhiro; Kawaguchi, Tatsuya; Schilthuizen, Menno (Zootaxa, 2007)
The synonymy of Perichaeta darnleiensis Fletcher, 1886, first described from Australian Darnley Island in the Torres Straits, was confused since Beddard (1900) and Michaelsen (1900) wrongly applied the names Perichaeta cingulata Schmarda, 1861 (= Megascolex cingulatus) and Megascolex indicus Horst, 1883 [= Amynthas corticis (Kinberg, 1828)], respectively. Taxonomic revision of this species now merges several parthenogenetic morphs, including Pheretima decipiens Beddard, 1912 syn. nov. from Luzon, Philippines. Final resolution depends on location of missing types or, alternatively, on neotypification, nevertheless new material from Mt. Kinabalu, north Sabah (Borneo) allows augmentation of the description of Pheretima darnleiensis from that given by Sims & Easton (1972) who, for its lobate/serrate intestinal caeca, remarked that these “cannot be regarded as taxonomic characters as they are more fully formed in the larger specimens”. Body size range is now 45–700 mm, although this suggests either high plasticity or too wide synonymy. Its distribution in the tropical Indo-Australasian Archipelago and islands of Malaysia, Indonesia and Fiji is attributed to human-mediated introductions in recent and pre-historic times that mask its true provenance; reports from Hawaii, Sri Lanka, South Africa and South America are disputed. Sympatric Amynthas omeimontis kinabalu Sims & Easton, 1972 was elevated to species level by Blakemore (2005). Descriptions of Pheretima (Parapheretima) saba Sims & Easton, 1972 and Polypheretima everetti (Beddard & Fedarb, 1895: 69) – somewhat similar to Polypheretima kinabaluensis (Beddard & Fedarb, 1895: 71) – are augmented and specimens are figured on newly collected material. A new Mt Kinabalu earthworm, Metaphire paka Blakemore sp. nov. is proposed that compares with Metaphire cai (Michaelsen, 1916) from Java [originally “Pheretima inflata (Horst) var. cai”], bringing the total known earthworms from Mt Kinabalu to six species. Ecological associations are briefly discussed.